2022
DOI: 10.1007/s00432-022-04495-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a metastasis-related diagnosis and prognosis model for lung adenocarcinoma through CRISPR library and TCGA database

Abstract: Purpose: Existing biomarkers for diagnosing and predicting the metastasis of lung adenocarcinoma (LUAD) may not meet the demands of clinical practice. Risk prediction models based on multiple markers may provide better prognostic factors for accurate diagnosis and prediction of metastatic LUAD.Methods: An animal model of LUAD metastasis was constructed using CRISPR library technology, and genes related to LUAD metastasis were screened by mRNA sequencing of normal and metastatic tissues.The immune characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…(2) Exclusion criteria: Patients with pneumonia, advanced liver disease, and severely abnormal liver function before treatment; patients with severe blood and immune system diseases before treatment and patients with other tumor diseases. Tumor metastasis: non-metastatic (0), metastasis to one organ (1), metastasis to two organs (2), and metastasis to three or more organs (3).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Exclusion criteria: Patients with pneumonia, advanced liver disease, and severely abnormal liver function before treatment; patients with severe blood and immune system diseases before treatment and patients with other tumor diseases. Tumor metastasis: non-metastatic (0), metastasis to one organ (1), metastasis to two organs (2), and metastasis to three or more organs (3).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“… 2 Many clinical studies have found that LC patients must achieve “three early”, that is, early detection, early diagnosis, and early treatment, in order to achieve good therapeutic results. 3 , 4 However, the prognosis for most LC patients is still very poor. This is mainly because the early symptoms of LC are not obvious and have been overlooked by patients, while when patients enter the hospital, about 75% of patients are already in the late stage of LC, and the prognosis of the late stage is relatively poor.…”
Section: Introductionmentioning
confidence: 99%